Sapienza Global Bedside Evaluation of Swallowing after Stroke: the GLOBE‐3S study. (3rd December 2018) - Toscano, M.; Viganò, A.; Rea, A.; Verzina, A.; Sasso D'Elia, T.; Puledda, F.; Longo, L.; Mancini, V.; Ruggiero, M.; Jannini, T. B.; Giuliani, G.; Albino, F.; et al.
Abstract : Background and purpose: Dysphagia occurs in up to 50% of all patients with acute stroke. There is debate regarding which is the most effective screening tool in identifying aspiration in patients with acute stroke. We assessed the accuracy of the Sapienza Global Bedside Evaluation of Swallowing after Stroke (GLOBE‐3S), which combines the Toronto Bedside Swallowing Screening Test (TOR‐BSST©) with oxygen desaturation and laryngeal elevation measurement during swallowing. Methods: We prospectively enrolled consecutive patients with stroke within 72 h of symptom onset. All patients with stroke firstly underwent a standard neurological examination, then the GLOBE‐3S evaluation and finally the fiberoptic endoscopic evaluation of swallowing (FEES). Two different assessors, a neurologist and a speech pathologist, blind to both the clinical data and each other's evaluation, administered the GLOBE‐3S and FEES examination. We assessed the accuracy of the GLOBE‐3S in detecting post‐stroke swallow impairment with aspiration using the FEES as the standard. Results: We enrolled 50 patients with acute stroke, 28 of whom (56%) had swallowing impairment with aspiration at FEES evaluation. A total of 33 patients (66%) failed the GLOBE‐3S evaluation. The GLOBE‐3S reached a sensitivity of 100% and a specificity of 77.3% (negative predictive value, 100%; positive likelihood ratio, 4.34). The median time required for the GLOBE‐3S to be performed was 297 s. Conclusions: GLOBE‐3S is quick to perform at the bedside and can accurately identify aspiration in patients with acute stroke. By including the measurement of laryngeal elevation and monitoring of oxygen desaturation, it could represent a highly sensitive instrument to avoid the misdiagnosis of silent aspirators.